Deliberate Practice and Proposed Limits on the Effects of Practice on the Acquisition of Expert Performance: Why the Original Definition Matters and Recommendations for Future Research - Ericsson, K. Anders; Harwell, Kyle W. (Frontiers in Psychology, 2019)
Over 25 years ago Ericsson, Krampe, and Tesch- Römer (1993) published their studies of “The role of deliberate practice in the acquisition of expert performance,” and much research has since been published on how attained level of performance is related to quantity, quality, and goals of accumulated practice activities. The original proposal for deliberate practice was the result of a search for conditions for optimal quality of practice during acquisition of expert performance in everyday life and eventually led to an analysis of the training of professional musicians, a domain where knowledge of effective training has been accumulated over centuries. At these academies, teachers provide students with individualized instruction and guide their solitary practice based on a curriculum—this form of effective training was named deliberate practice. When other researchers began searching for similar types of optimal training conditions in sports, they had difficulties finding practice activities meeting the definition of deliberate practice and therefore proposed different criteria while still referring to the activities as “deliberate practice”. This paper recommends giving unique names to categorically different practice activities and reports meta-analyses showing that the accumulation of these different practice types has strikingly different effects on attained performance. When we analyzed only studies matching the criteria for the original definitions of deliberate or purposeful practice, we found that practice explained considerably more variance in performance (29% and 61% after attenuation) than had been previously reported (14%) by Macnamara, Hambrick, & Oswald (2014, 2018). We also review current reproducible evidence from studies of genetics, which suggests the effects of height and body size do constrain attainable performance, but other genetic effects account for remarkably small amounts of variance. The paper concludes with recommendations for how future research on purposeful and deliberate practice should look deeper and describe the detailed practice activities of elite performers. Based on this type of data, researchers will be able to infer essential conditions for optimal practice that can inform, not just athletes and their coaches, but all motivated individuals about how their achievements can be improved with particular types of training.